The effect of increasing physiological arousal on badminton short serve accuracy during competition and practice - Duncan, M. J.; Chan, K.; Smith, M.; Clarke, N. D. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Perceptual-motor performance has been suggested to be negatively impacted in situations where physiological arousal is increasing and cognitive anxiety is high compared to when cognitive anxiety is low (Duncan et al., 2016). In such cases, competition has been used to elicit high anxiety and practice low anxiety. The aim of this study was to examine the effect of increasing physiological arousal on badminton short serve accuracy during competition and practice. Methods: Following ethical approval, informed consent and familiarisation, 19 competitive badminton players (10 males; 9 females, mean±SD playing experience: 7.3±3y, mean±SD age: 19±1 y) participated in this counterbalanced study. Players completed the Edwards et al (2005) short serve accuracy test pre and post, the Bottoms et al (2012) Badminton fatigue protocol on two occasions; competition (high cognitive anxiety) and practice (low cognitive anxiety). Heart rate (HR) was monitored throughout and RPE was assessed at 6 points during the 33min protocol. Cognitive anxiety, somatic anxiety and self-confidence were measured pre and post the fatigue protocol and prior to completion of the badminton short-serve test. Results: Results from a 2(competition vs practice) X 2(pre vs post) way repeated measures ANOVA revealed a significant main effect for competition vs practice where short serve performance was significantly poorer in competition compared to practice (P = .025). Cognitive anxiety intensity increased pre to post fatigue in competition (P = .001) but not practice (P = .521) conditions. Somatic anxiety intensity increased pre to post for both conditions (P = .008). HR was not different between conditions (P =.460). RPE was significantly higher in competition compared to practice (P = .01). HR and RPE increased with duration of the fatigue protocol irrespective of condition (both P = .001). There were no changes in self-confidence across time or condition (P>.05). Discussion: These results suggest that badminton service performance is negatively affected in conditions where cognitive anxiety is high (competition) compared to when cognitive anxiety is low (practice). RPE was also higher where cognitive anxiety was high (competition) despite no differences in actual physiological load during the fatigue protocol. As such, we propose that the relationship between perceptual change and cognitive anxiety is the decisive factor in predicting decrements in badminton short serve performance